2013
DOI: 10.1186/1475-2875-12-189
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility to quinine and microsatellite variations of the Plasmodium falciparum Na+/H+ exchanger transporter (Pfnhe-1) gene in 393 isolates from Dakar, Senegal

Abstract: BackgroundAlthough the World Health Organization recommends replacing quinine (QN) by artesunate due to its increased efficacy and the higher tolerance to the drug in both adults and children, QN remains a first-line treatment for severe malaria, especially in Africa. Investigations of microsatellite Pfnhe-1 ms4760 polymorphisms in culture-adapted isolates from around the world have revealed that an increase in the number of DNNND amino acid motifs was associated with decreased QN susceptibility, whereas an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
3
7
1
Order By: Relevance
“…Though QN was not used in the Yekepa area at the time of this study the frequency of pfnhe1 ms4760-1 (26%) was similar to the frequency found at day 0 in a recent study in Mali where ms4760-1 was associated with QN resistance [97]. Furthermore, the number and frequencies of DDNHNDNHNND repeats in this study were similar to data found in 393 clinical isolates recently reported from Senegal [286]. Despite the geographic separation, the similarity to that found in Liberia in 1978 , prior to a drug selective pressure, suggests that ms4760-1 did not play a significant role in the emergence of resistance in West Africa over subsequent years.…”
Section: P Falciparum Na+/h+ Exchanger-1supporting
confidence: 88%
See 1 more Smart Citation
“…Though QN was not used in the Yekepa area at the time of this study the frequency of pfnhe1 ms4760-1 (26%) was similar to the frequency found at day 0 in a recent study in Mali where ms4760-1 was associated with QN resistance [97]. Furthermore, the number and frequencies of DDNHNDNHNND repeats in this study were similar to data found in 393 clinical isolates recently reported from Senegal [286]. Despite the geographic separation, the similarity to that found in Liberia in 1978 , prior to a drug selective pressure, suggests that ms4760-1 did not play a significant role in the emergence of resistance in West Africa over subsequent years.…”
Section: P Falciparum Na+/h+ Exchanger-1supporting
confidence: 88%
“…Eight of the 114 previously described pfnhe1 variants [97,249] [75,97,249,286]. Though QN was not used in the Yekepa area at the time of this study the frequency of pfnhe1 ms4760-1 (26%) was similar to the frequency found at day 0 in a recent study in Mali where ms4760-1 was associated with QN resistance [97].…”
Section: P Falciparum Na+/h+ Exchanger-1supporting
confidence: 73%
“…LUM, MQ and PiP are partner drugs in ACT and all of them had a relatively low mean IC 50 , the first two around 1 nM and the latter at 5.0 nM. In addition, DHA’s mean IC 50 was also low, confirming earlier reports from other parts of Burkina Faso as well as other sub-Saharan African countries [ 17 , 33 35 ]. This suggests that the efficacy of both AL and AS–AQ should be good as most parasite isolates were sensitive to both components of the two ACT.…”
Section: Discussionsupporting
confidence: 83%
“…QN susceptibility was previously associated with microsatellite repeats in P. falciparum Na ϩ /H ϩ exchanger 1 (Pfnhe-1) (14,15). However, this association was location specific and differed between African and Asian P. falciparum isolates (15)(16)(17). The low number of P. falciparum isolates and the modest association limited the interpretation of the present results.…”
Section: Role Of Pfmdr6 In Antimalarial Susceptibilitycontrasting
confidence: 51%